Adolescents and photoblogs: Building identity through play - Lydia Sánchez; Sílvia Burset (Digithum, 2009)
The internet has led to a new paradigm in interpersonal relationships, especially among the young. In this article, we analyse, from a theoretical and speculative perspective, the interaction of two agents in the phenomenon of communication: adolescents and photoblogs. A photoblog is a virtual tool that the young of between around thirteen and sixteen years of age have adapted to their needs to express ideas, feelings or fantasies. We believe that, in this setting, subjects can communicate in a space where they explore their "inner me" through representation, signs and symbols shown in the interface. Nowadays, adolescents live in an eminently visual context and, thus, it should come as no surprise that their actions and communication should centre on "the visual", where the linear and foreseeable are superseded by speed, feedback and continuity. The formalisations are seen in the interface where the codes that the young themselves have created are used to reflect identifying traits through images. Thus, we believe that adolescents see photoblogs not just as the media, but also as the environment in which they can create identifying traits through virtual conversations with their peers in an uninhibited leisure setting, where they can play with their image in a process of socialisation.